Über Zusammenhänge in Lieschen Gruppen - Vosylius, R. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. В. Восилюс. О связностях на группах Ли R. Vosylius. Apie sąryšius Li grupėse